Sex-dependent effects of chronic stress on reinstatement of palatable food seeking and involvement of dopamine D(1)-like receptors - Ball, Kevin T. (Behav Brain Res, 2020)
Recent work in our lab has shown that chronic stress exposure causes sex-dependent changes in subsequent relapse-like behavior in rats with a history of palatable food self-administration. Although these effects are mediated by dopamine D(1)-like receptors in male rats, such dopaminergic mechanisms have not been investigated in female animals. Thus, male and female rats were trained to respond for highly palatable food reinforcers in daily sessions. During subsequent extinction training, stress was manipulated (0 or 3 hr restraint/day for 7 days). To assess dopaminergic involvement, we administered either SCH-23390 (10.0 μg/kg), a dopamine D(1)-like receptor antagonist, or vehicle prior to daily treatments. Rats were then tested for cue- and pellet priming-induced reinstatement. Results showed that a history of chronic stress caused an increase in pellet priming-induced reinstatement in males and a decrease in cue-induced reinstatement in females. SCH-23390 combined with stress prevented those effects in males, but not in females. In females, a history of SCH-23390 administration caused an overall increase in responding that was apparent during cue-, but not pellet priming-, induced reinstatement testing. These results establish that both the effects of chronic stress on reinstatement of food seeking and the involvement of dopamine in those effects are dependent on biological sex. Such findings should inform the development of sex-specific interventions for dietary relapse and other stress-related health problems.